An Empirical Study on Various Healthcare Strategies Followed by Selected Hospitals in Puducherry - Kumar K, Nikhil; Anand, Byram (Management Journal for Advanced Research, 2023)
India is a prime example of a nation that has seen significant change in the expansion of the global healthcare industry. It is a nation with a wealth of medical expertise and ability, giving it an advantage in the medical industry through a variety of health service offerings. Patients from all over the world come India for treatment due to its medical expertise. However, the rate of development in the Indian medical industry does not reflect the reality that it has faced numerous challenges both historically and currently. Even though India is one of the biggest providers of health care services, it still has many flaws, including unregulated competition, poor service quality, high costs, the dominance of private health care players, insufficient resources, a narrow focus, and a deteriorating public health care sector. Aside from this, it is a common rural-urban imbalance that rural areas have far less access to medical care than metropolitan ones. As a result, there is a considerable demand for health care, yet there are insufficient financial and administrative resources to satisfy it. In this regard, the current study aims to evaluate different healthcare practices used by a chosen hospital in Puducherry.